Narradores ecuatorianos de la década de 1950: poéticas para la lectura de modernidades periféricas - Rodríguez, Martha (2024)
Published between 1945-1962, the works of these writers went much further in terms of some of the problems raised by the narrators of the 1950s. Having assumed its class extraction, questions addressing their own identity, the plight of the mestizo, their role as writers, the impact of the incipient modernity that de-structured daily life in their villages and cities were also raised. Therefore, they agree with the thematic of Latin American narrators of that period, who maintained in the aesthetic the tension between regionalism and vanguard; the Ecuadorians redefined themselves within a realism that gave space to lyricism, although Latin American vanguards were also being observed from different angles. César Dávila Andrade posed an aesthetic of the «supra-rea» horror, Ángel F. Rojas in modern times addressed themes related to regionalism, Walter Bellolio summarized the best of the narrative vanguard and the Ecuadorian tradition of storytelling, Alfonso Cuesta y Cuesta configured an aesthetic of the enlightened metaphors, and Arturo Montesinos dealt with the metaphor from the split that brings every modernity, without taking into account how peripheral and incipient that it may appear.